SYNTHESIS AND CHARACTERIZATION OF CALCIUM SILICATE FROM RICE HUSK ASH AND SNAIL SHELL - Husain, Sadang; Haryanti, Ninis Hadi; Suryajaya, Suryajaya; Permitaria, Antung (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2019)
Calcium silicate ceramics have been made using natural ingredients such as rice husk and snail shell with solid reaction techniques. The aim of this study to determine the characteristics of calcium silicate that have been sintered at a temperature of 900 °C, 1000 °C, and 1100 °C. Samples were characterized by X-Ray Diffraction (XRD), optical microscopy, and Fourier Transform Infra-Red (FTIR). The results of XRD characterization showed that CaSiO3 (calcium silicate) along with the increase in calcination temperature and quantity was increased due to the increase of temperature of calcination. FTIR analysis showed that the Ca-Si-O bond was formed at wave number ranging from 848 cm-1 and 999 – 1001 cm-1.